2022
DOI: 10.1155/2022/8744788
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Edible Mushroom on Health and Their Biochemistry

Abstract: Edible mushrooms are fungi that can be seen with the naked eye and are relatively easy to gather by hand. This review article highlights the health benefit and the biochemistry of several mushroom species. Agaricus bisporus, Pleurotus species. Lentinus edodes, and Volvariella species are the most acceptable varieties among the cultivated mushroom. Various biochemical methods such as methanol, ethanol, and water extract of different parts of the edible mushroom in the laboratory have been applied to determine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 67 publications
(55 reference statements)
0
34
0
Order By: Relevance
“…The easily digestible proteins of mushrooms are determined as the main carrier of the mushroom’s nutritional value because they could provide all essential amino acid requirements [ 68 ]. Apart from the nutritional value, there are reports about bioactive proteins and peptides demonstrating pharmacological potential [ 68 , 85 , 86 , 87 ]. The protein content of the wild fruiting body and mycelium biomass obtained through submerged cultivation usually varies.…”
Section: Resultsmentioning
confidence: 99%
“…The easily digestible proteins of mushrooms are determined as the main carrier of the mushroom’s nutritional value because they could provide all essential amino acid requirements [ 68 ]. Apart from the nutritional value, there are reports about bioactive proteins and peptides demonstrating pharmacological potential [ 68 , 85 , 86 , 87 ]. The protein content of the wild fruiting body and mycelium biomass obtained through submerged cultivation usually varies.…”
Section: Resultsmentioning
confidence: 99%
“…The fact is that glucans have a positive effect on human health [ 5 , 54 , 55 ]. However, the priority scientific focus is on β-glucans.…”
Section: Resultsmentioning
confidence: 99%
“…According to [5], in recent decades the use of mushrooms has interestingly increased in the pharmaceutical industry, nutraceutical, and cosmeceutical business sectors. Edible mushrooms are more highly nutritional than any fruits and vegetables and have been eaten for their texture and enjoyable flavor, and therapeutic properties for many years [6]. e study reported that there are several oyster mushroom species i.e., Agaricus bisporus, Pleurotus species, Lentinus edodes, and Volvariella species which are the most acceptable varieties among the cultivated mushroom considering their health benefit and the biochemistry properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…ostreatus cultivation has so many advantages over other edible mushrooms [8]. ese are as follows: (1) grows fast under a wide range of temperatures (10 °C to 30 °C) and pH (6)(7)(8) [8], (2) secretes a wide range of enzymes that are capable of degrading lingo-cellulosic biomass of substrates [12], (3) has high-yield potential and high nutritional value and medicinal importance, (4) demands a few environmental control, (5) can colonize substrates in a shorter time, and (6) does not need composting of its substrate. Moreover, their fruiting bodies are not often attacked by any diseases and pests, they can be cultivated in general in simple and cheap ways, and their cultivation needs only pasteurization which is cheap and does not require a more expensive method like sterilization [8].…”
Section: Introductionmentioning
confidence: 99%